Foreign Tourists in World Heritage Sites: A Motivation-Based Segmentation - Antonio Menor-Campos (Sustainability, 2020)
The inclusion on the lists published by the United Nations Educational, Scientific, and Cultural Organization (UNESCO)—World Heritage Site (WHS), Intangible Cultural Heritage (ICH), and World Heritage Sites in Danger—suggests, first of all, the acknowledgement of something worth protecting and, secondly, an increase in the strength of tourist attraction to the affected destination, especially among specific visitors. The identification and classification of tourists that are seen to be more interested in heritage is the stated aim of this work, based on models already proposed in the scientific literature. For this purpose, a survey was conducted that interviewed a representative sample of international tourists visiting the city of Córdoba. A multi-variant technique of case-cluster was applied. In addition, a discriminant analysis was used to validate the clusters of the cases obtained. For analyzing the differences between the different groups obtained, some non-parametrical statistical procedures were applied. The results obtained allowed for the visualization of a model that shows the empirical evidence regarding the presence of four types of foreign tourists that are considered valid for segmentation in the city of Córdoba as a WHS tourist destination: the alternative tourist, emotional tourist, cultural tourist, and heritage tourist. These results allow public and private managers to design specific strategies to increase visitor satisfaction.